Pendidikan Karakter dan Implementasinya - Edison Edison (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of writing this article is to introduce the concept of character education and its implementation in schools. The method used in writing this article is the method of literature study or literature study. The results of the study, character education in essence aims to form a strong, competitive, noble, moral, tolerant, mutual cooperation, patriotic spirit, dynamic developing, oriented to science and technology which are all imbued with faith and piety to God Almighty based on Pancasila . Character education functions (1) develops the basic potential to be kind, think well and behave well (2) strengthen and build multicultural behavior of the nation, (3) enhance the nation's competitive civilization in the world. Conclusion, character education efforts are carried out on children from an early age through various media that include families, civil society education units, government communities, the business world and mass media. Keywords: Character Education, Implementation